To determination of the stability of an articulated bus with a self-aligning trailer axle - Sakhno, Volodymyr; Murovanyi, Igor; Kotenko, Andrii (Видавництво Львівської політехніки, 2025)
Останнім часом шарнірно-зʼєднані автобуси (ШЗА), місткість яких 150–200 осіб, все ширше застосовують у пасажирських перевезеннях. Габаритна довжина таких автобусів обмежена на рівні 18,5 м, що пояснюється необхідністю дотримання нормативних вимог щодо маневреності. В Україні Правилами дорожнього руху дозволена загальна довжина автопоїзда на рівні 22 м. За такої довжини пасажиромісткість ШЗА істотно збільшується, проте відкритими залишаються питання маневреності та стійкості руху таких автобусів. Попередніми дослідженнями показано, що навіть автобус загальною довжиною 18,75 м з некерованою віссю причепа не задовольняє вимоги нормативних документів щодо маневреності. Застосування самоустановлювальної осі причепа задовольняє вимоги щодо маневреності навіть за довжини ШЗА до 20,0 м, проте залишається відкритим питання щодо стійкості такого автобуса. За уточненою математичною моделлю дволанкового автопоїзда, адаптованою для ШЗА з самоустановлювальною віссю причепа, визначено показники стійкості шарнірно-зʼєднаного автобуса у різних режимах руху. Показано, що критична швидкість ШЗА із заблокованими колесами самоустановлювальної осі причепа досягає 31,87 м/с, що істотно перевищує максимальну швидкість руху автобуса. За наявності збурення зміна бічної та кутової швидкостей ШЗА у часі перехідного процесу за швидкості 6 м/с згасає за логарифмічним законом, що свідчить про стійкість руху ШЗА. У разі збільшення швидкості до 12 м/с зміни бічної та кутової швидкостей також згасають, але спостерігаються інтенсивніші коливання, які за швидкості 14 м/с стають розбіжними, що призводить до втрати стійкості руху ШЗА. Аналогічні результати отримані й у разі повороту ШЗА на 900. Отже, гранична швидкість руху ШЗА із розблокованими колесами самоустановлювальної осі причепа не повинна перевищувати 14 м/с. Після досягнення цієї швидкості колеса самоустановлювальної осі повинні блокуватися. Це зумовлює галузь застосування самоустановлювальної осі причепа на шарнірно-зчленованих автобусах. Для руху із вищими швидкостями необхідні принципово нові системи управління автобусом і причепом ШЗА.

Recently, articulated buses with a capacity of 150-200 people have been increasingly used in passenger transportation. The overall length of such buses is limited to 18.5 meters. It is explained by the need to meet regulatory requirements for maneuverability. In Ukraine, the Road Traffic Rules allow the total length of a road train to be 22 meters. With this length, the passenger capacity of the articulated bus increases significantly, but the issues of maneuverability and stability of such buses remain open. Preliminary studies have shown that even a bus with a total length of 18.75 m with an unmanageable trailer axle does not meet the requirements of regulatory documents for maneuverability. Using a self-aligning trailer axle meets the requirements for maneuverability even with an articulated bus length of up to 20.0 m. Still, the question of the stability of such a bus remains open. Using a specified mathematical model of a two-link road train adapted for an articulated bus with a self-aligning trailer axle, the stability indicators of an articulated bus in different driving modes were determined. It is shown that the critical velocity of the articulated bus with the blocked wheels of the trailer's self-aligning axle was 31.87 m/s, which significantly exceeds the maximum velocity of the bus. In the presence of a perturbation, the pattern of changes in the lateral and angular velocities of the articulated bus during the transition process at a velocity of 6 m/s is damped by a logarithmic law, which indicates the stability of the articulated bus movement. When the velocity is increased to 12 m/s, the pattern of changes in lateral and angular velocities also dampens. Still, there are more intense oscillations, which at a velocity of 14 m/s become divergent, leading to a loss of stability of the articulated bus. Similar results were obtained when the rotation of the articulated bus was 90 degrees. Thus, the maximum velocity of the articulated bus with unlocked wheels of the trailer's self-aligning axle should not exceed 14 m/s. When this velocity is reached, the wheels of the self-aligning axis should lock. It determines the field of application of the self-aligning trailer axle on articulated buses. For driving at higher velocities, fundamentally new control systems for the bus control and the articulated bus trailer are needed.
До визначення стійкості руху шарнірно-зʼєднаного автобуса із самоустановлювальною віссю причепа
Keywords: шарнірно-зʼєднаний автобус; причіп; самоустановлювальна вісь; швидкість; збурення; коливання; стійкість; articulated bus; trailer; self-aligning axle; velocity; perturbation; oscillations; steadiness